2010
DOI: 10.1534/genetics.110.120014
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Size of Populations Infected With Cytoplasmic Sex-Ratio Distorters

Abstract: Many arthropod species are infected with maternally inherited endosymbionts that induce a shift in the sex ratio of their hosts by feminizing or killing males (cytoplasmic sex-ratio distorters, or SRDs). These endosymbionts can have profound impacts on evolutionary processes of their hosts. Here, I derive analytical expressions for the coalescent effective size N e of populations that are infected with SRDs. Irrespective of the type of SRD, N e for mitochondrial genes is given by the number of infected females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…We also confirmed that this formula can be derived by substituting χ i = t (1 + B )/2 and χ u = χ m = (1 − t )(1 + B )/2 into Engelstädter's (2010) formula [Note that his original formula is incorrect and the correct one is given in a recently published errata note (Genetics 186, pp. 2503)].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We also confirmed that this formula can be derived by substituting χ i = t (1 + B )/2 and χ u = χ m = (1 − t )(1 + B )/2 into Engelstädter's (2010) formula [Note that his original formula is incorrect and the correct one is given in a recently published errata note (Genetics 186, pp. 2503)].…”
Section: Discussionsupporting
confidence: 65%
“…First, let us consider the calculation of the effective population size of the island population. Recently, Engelstädter (2010) has obtained a formula of effective population size applicable to various kinds of cytoplasmic sex‐ratio distorters. Here, we instead use a more general formula for a class‐structured population, which was derived by previous authors (Nagylaki, 1980; Nordborg & Krone, 2002; Rousset, 2004; Sjödin et al.…”
Section: Resultsmentioning
confidence: 99%
“…Whilst the hypothesis that endosymbiont driven changes in behaviour can lead directly to reproductive isolation is difficult to test, it is certainly true that changes in both reproductive and non-reproductive behaviours such as mating preference or dispersal likely influence genetic diversity at a local scale. For instance restriction in the number of successfully reproducing individuals via male-killing or CI will lower the effective population size [ 25 ]. Such impacts on population size and the various impacts on reproductive traits will have further consequences for the local intensity and dynamics of sexual selection and conflict [ 26 , 27 , 28 ].…”
Section: The Evolutionary Consequences Of Endosymbiont Driven Chanmentioning
confidence: 99%
“…Male-killing can increase infected female fitness at the expense of non-transmitting infected males by increasing the resources available to females, either by reducing inter-sibling competition or via cannibalism [ 1 ]. Endosymbionts that have near-perfect transmission may reduce the effective population size ( N e ) by a factor that approximates to the proportion of uninfected individuals in the population [ 2 ]. Theoretical studies of male-killing endosymbionts, where hybridizing subpopulations interbreed, have shown that local adaptation can be strongly impeded in the subpopulation with the more biased population sex ratio [ 3 ].…”
Section: Introductionmentioning
confidence: 99%